Investigation of the Bioactivity Properties of TiZrCrNb0.3Ta0.07 Medium Entropy Alloy Produced from TNTZ Waste - Yayla, Nihal; Güler, Ömer; Say, Yakup; Güzel, Harun (Fırat University, 2025)
High entropy alloys (HEAs) and medium entropy alloys (MEAs) have garnered significant attention as alternative materials in various fields due to their superior physical and chemical properties compared to conventional alloys. One of the most promising applications of this innovative material class is in biomaterials. In this study, a bio-medium entropy alloy (BioMEA), TiZrCrNb0.25Ta0.05, was successfully synthesized using non-toxic elements (Ti, Zr, Cr, Nb and Ta) through arc melting of TNTZ alloy waste. The produced BioMEA was comprehensively characterized using scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), and X-ray diffraction (XRD) to analyze its structural and chemical properties. Additionally, the in-vitro degradation, ion release, and bioactivity properties of the alloy were evaluated and compared with those of the conventional TNTZ alloy, with a focus on the effects of heat treatment. The results demonstrated that heat treatment did not cause significant changes in the microstructure of the TiZrCrNb0.25Ta0.05 alloy but led to the formation of intermetallic compounds such as Cr2Zr and Cr2Ta on the surface. Degradation tests revealed an unexpected mass gain across all sample groups after a four-week immersion period due to surface precipitation, surpassing the expected mass loss from degradation. Ion release analyses showed similar behavior between the TiZrCrNb0.25Ta0.05 and TNTZ alloys, with ion release levels in the ppb range, confirming that Ti was released at non-toxic levels. Bioactivity tests identified low lesvels of Ca-P-O deposition on all sample surfaces, with the highest bioactivity observed in the heat-treated TiZrCrNb0.25Ta0.05 sample. Overall, the findings suggest that the TiZrCrNb0.25Ta0.05 alloy has the potential to serve as an alternative biomaterial to the TNTZ alloy, with its bioactivity properties being further enhanced through heat treatment. Further studies are recommended to optimize its bioactivity and evaluate its in-vivo performance for biomedical applications.

Yüksek entropili alaşımlar ve orta entropili alaşımlar, üstün fiziksel ve kimyasal özellikleri sayesinde geleneksel alaşımlara kıyasla çeşitli alanlarda alternatif malzemeler olarak önemli bir ilgi görmektedir. Bu yenilikçi malzeme sınıfının en umut verici uygulama alanlarından biri biyomalzemelerdir. Bu çalışmada, toksik olmayan elementler (Ti, Zr, Cr, Nb ve Ta) kullanılarak, TNTZ alaşımı atığından ark ergitme yöntemiyle başarıyla sentezlenen bir biyo-orta entropili alaşım, TiZrCrNb0.25Ta0.05, elde edilmiştir. Üretilen biyo-orta entropili alaşımın yapısal ve kimyasal özellikleri; taramalı elektron mikroskobu, enerji saçınımlı X-ışını spektroskopisi ve X-ışını difraksiyonu teknikleriyle kapsamlı bir şekilde karakterize edilmiştir. Ayrıca, alaşımın in-vitro degradasyon davranışı, iyon salınımı ve biyouyumluluğu değerlendirilmiş ve bu özellikler ısıl işlemin etkisi dikkate alınarak konvansiyonel TNTZ alaşımıyla karşılaştırılmıştır. Elde edilen sonuçlar, ısıl işlemin TiZrCrNb0.25Ta0.05 alaşımının mikroyapısında belirgin bir değişikliğe yol açmadığını, ancak yüzeyde Cr2Zr ve Cr2Ta gibi intermetalik fazların oluşumuna neden olduğunu göstermiştir. Degradasyon testleri, dört haftalık daldırma süreci sonunda tüm numune gruplarında beklenen kütle kaybının aksine, yüzeydeki çökelmelere bağlı olarak net kütle artışı gözlemlendiğini ortaya koymuştur. İyon salınım analizlerinde, TiZrCrNb0.25Ta0.05 ve TNTZ alaşımlarının benzer davranışlar sergilediği ve iyon salınım seviyelerinin ppb aralığında olduğu tespit edilmiş; özellikle salınan titanyum iyonlarının toksik olmayan düzeylerde olduğu doğrulanmıştır. Biyouyumluluk testlerinde, tüm numunelerin yüzeylerinde düşük seviyede Ca-P-O birikimi gözlemlenmiş; en yüksek biyouyumluluk ise ısıl işlem uygulanmış TiZrCrNb0.25Ta0.05 numunesinde saptanmıştır. Genel olarak, elde edilen bulgular TiZrCrNb0.25Ta0.05 alaşımının TNTZ alaşımına alternatif bir biyomalzeme olarak kullanılabileceğini ve ısıl işlemle biyouyumluluğunun daha da artırılabileceğini göstermektedir. Biyolojik uygulamalarda in-vivo performansının değerlendirilmesi ve biyouyumluluğunun optimize edilmesi için ileri düzey çalışmalar önerilmektedir.
TNTZ Atıklarından Üretilen TiZrCrNb0.3Ta0.07 Orta Entropili Alaşımın Biyoaktivite Özelliklerinin Araştırılması
Keywords: Materials Engineering (Other); Malzeme Mühendisliği (Diğer)